The incorporation of young people from the community El Raposo to recreational physical activities - Ramón Tomás Beltrán-Domínguez (Universidad de Guantánamo, 2012)
The problems discussed in this article have to do with how to increase the young people's incorporation to the physical recreational activities in the community Raposo of the municipality of Guantánamo, in order to contribute to occupy free time healthily. The fundamental contribution of the paper is an educational strategy with a scientific pedagogic updated foundation, and a system of actions that integrate the physical recreational communal influences coherently-recreational and educational aspects that contribute to transforming attitudes and young people's conducts in this community through their incorporation in a conscious and voluntary way to physical practices.